Optimization of bioethanol production from saccharified sweet potato root flour by co-fermentation of Saccharomyces cerevisiae and Pichia sp. using OVAT and response surface methodologies - Dash, Preeti Krishna; Mohaptra, Sonali; Swain, Manas Ranjan; Thatoi, Hrudayanath (Acta Biologica Szegediensis, 2017)
In recent years with the increase in price of fossil fuels, the demand of biofuel production from tuber crops such as sweet potato has become very important to meet the future energy crisis in developing countries. In the present study, fermentation of saccharified sweet potato root flour (SPRF) was carried out using co-culture of cells of Saccharomyces cerevisiae and Pichia sp. in immobilized condition for bioethanol production. Various growth parameters like incubation time, fermentation medium pH, incubation temperature and inoculum size were initially optimized using one variable at a time (OVAT) methodology. Then, temperature, pH and incubation time were found to be the most favorable variables for the maximum ethanol production with Box-Behnken design of response surface methodology (RSM). The maximum ethanol yield of 127.2 ± 2 g/kg of SPRF was obtained at pH 5 with an incubation period of 72 h at 30 °C by OVAT methodology. RSM further enhanced the bioethanol yield to 138.6 ± 3 g/kg of SPRF with an overall increase of 8.22% as compared to the OVAT method.